Microarray based comparative genomic hybridization testing in deletion bearing patients with Angelman syndrome: genotype-phenotype correlations. Issue 6 (23rd September 2005) - Sahoo, T; Peters, S U; Madduri, N S; Glaze, D G; German, J R; Bird, L M; Barbieri-Welge, R; Bichell, T J; Beaudet, A L; Bacino, C A
Abstract : Background: Angelman syndrome (AS) is a neurodevelopmental disorder characterised by severe mental retardation, dysmorphic features, ataxia, seizures, and typical behavioural characteristics, including a happy sociable disposition. AS is caused by maternal deficiency of UBE3A (E6 associated protein ubiquitin protein ligase 3A gene), located in an imprinted region on chromosome 15q11-q13. Although there are four different molecular types of AS, deletions of the 15q11-q13 region account for approximately 70% of the AS patients. These deletions are usually detected by fluorescence in situ hybridisation studies. The deletions can also be subclassified based on their size into class I and class II, with the former being larger and encompassing the latter. Methods: We studied 22 patients with AS due to microdeletions using a microarray based comparative genomic hybridisation (array CGH) assay to define the deletions and analysed their phenotypic severity, especially expression of the autism phenotype, in order to establish clinical correlations. Results: Overall, children with larger, class I deletions were significantly more likely to meet criteria for autism, had lower cognitive scores, and lower expressive language scores compared with children with smaller, class II deletions. Children with class I deletions also required more medications to control their seizures than did those in the class II group. Conclusions: There are four known genes ( NIPA1, NIPA2, CYFIP1, & GCP5 ) that are affected by class I but not class II deletions, thus raising the possibility of a role for these genes in autism as well as the development of expressive language skills.